The role of accountability at work in career work at work: "A case study of a sample of employees of Imam Al-Kadhim University in Babylon" - aliwi sahib, Hassan; hatef Al.fatlawy, Meethaq (Iraqi Journal for Administrative Sciences, 2024)
This research seeks to interpret, translate and develop the relations between work and cooperation in the development of work in the field of work in the College of Imam Al-Kadhim "peace be upon him" after the work of building the image in a good image began, this image was full in 2010, and based on talents from the community Al-Iraqi, and to achieve this, the researcher distributed (58) questionnaires to a number of employees, where the retrieved questionnaires were (55) questionnaires, while the number of questionnaires valid for statistical analysis was (53) (my promotion questionnaire) (98%) of the retrieved questionnaires. The results showed that there is a knowledge gap in explaining the relationship between workers at work and withdrawal from work in the working organization. So is workplace accountability and opt-out.